Young children's transmission of information following self-discovery and instruction - Karadağ, Didar; Bazhydai, Marina; Westermann, Gert (Frontiers in Developmental Psychology, 2025)
Children acquire knowledge through both independent exploration and other's instruction. While previous research suggests that children treat these sources of information differently, little is known about how they convey such knowledge to others. The current study investigated whether children distinguish between self-explored and instructed information when teaching a naïve learner and how this distinction may change as they develop. Two- and 5-year-old children (N = 82; 37 females; predominantly White) were shown novel boxes with distinct functions, which they learned about through either self-exploration or direct instruction. In a subsequent teaching phase, children were asked to demonstrate the boxes' functions to a naive adult. The results showed that 2-year-olds were more likely to demonstrate the instructed function first compared to the self-explored function (Cohen's d = 0.55), whereas five-year-olds showed no such preference. These findings suggest that socially acquired information carries different saliency for toddlers and older children, contributing to the under-investigated field of children's teaching in early childhood.